|
|
|
@ -73,7 +73,7 @@ Hint (n : ℕ) (hn : 2 * ∑ i : Fin (n + 1), ↑i = n * (n + 1)) :
|
|
|
|
|
Hint (n : ℕ) (hn : 2 * ∑ i : Fin (n + 1), ↑i = n * (n + 1)) :
|
|
|
|
|
2 * (∑ x : Fin (n + 1), ↑x + (n + 1)) = Nat.succ n * (Nat.succ n + 1) =>
|
|
|
|
|
"Um Die Induktionshypothese anzuwenden muss man noch
|
|
|
|
|
$$2 \\cdot ((\\sum_{x=0}^n x) + (n + 1)) = 2 \\cdot \\sum_{x=0}^n x + 2 \\cdot (n + 1))$$
|
|
|
|
|
$$2 \\cdot ((\\sum_\{x=0}^n x) + (n + 1)) = 2 \\cdot \\sum_\{x=0}^n x + 2 \\cdot (n + 1))$$
|
|
|
|
|
umschreiben. Dazu kannst du `mul_add` benützen.
|
|
|
|
|
"
|
|
|
|
|
|
|
|
|
|